2015
DOI: 10.17155/spd.67561
|View full text |Cite
|
Sign up to set email alerts
|

Üni̇versi̇te Öğrenci̇leri̇ni̇n Beslenme Alişkanliklarinin İncelenmesi̇: Ondokuz Mayis Üni̇versi̇tesi̇ Örneği̇

Abstract: ÖZETBu araştırma, Ondokuz Mayıs Üniversitesi'nde öğrenim gören öğrencilerin sağlıklı yaşam gereklerine uyma durumları ile beslenme bilgi ve alışkanlıklarını belirleme amacını taşımaktadır. Çalışmaya 2013-2014 Eğitim Öğretim yılında Ondokuz Mayıs Üniversitesi'nin 48 farklı bölümünde öğrenim gören toplam 1105 öğrenci gönüllü olarak katılmıştır. Çalışmanın verileri, öğrencilerin sosyo-demografik bilgileriyle beraber beslenme alışkanlıkları ile ilgili soruları da içeren anket formu ile toplanmıştır. Verilerin anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 3 publications
0
15
1
17
Order By: Relevance
“…The most skipped meal is lunch, by the ratio of 52.3%. Again, the proportion of skipped meal among students was 52.6% and it was lunch [50]. Compared to other study results in Turkey, it has been seen that university students who participated to the study skip meals less than the others.…”
Section: Discussioncontrasting
confidence: 62%
“…The most skipped meal is lunch, by the ratio of 52.3%. Again, the proportion of skipped meal among students was 52.6% and it was lunch [50]. Compared to other study results in Turkey, it has been seen that university students who participated to the study skip meals less than the others.…”
Section: Discussioncontrasting
confidence: 62%
“…When the underlying reasons of the negative changes were examined, "non-behaviourual foods" (%32.5), "difficulty of preparation" (%27.7) and "shortage of time" (%27.7) took in the first place (Table 2). Meal skipping, unhealthy snacks, frequently fast-food consumption, decreased fruit and vegetable consumption described as the reasons of negative changes in most of the previous studies (Ansari et al 2012;Bellisle et al 1995;Ermiş et al 2015;Ilow 2005;Kasparek et al 2008;Mazıcıoğlu and Öztürk 2003). Ayhan et al (2012) in their study, the responses they received when they asked the reasons of the unhealthy and irregular behaviours were "shortage of time" (%69.0), "inappetence and reluctance" (%31.2) and "difficulty in reaching favourite foods" which were similar with this study.…”
Section: Discussionmentioning
confidence: 95%
“…Zaybak and Fadıloğlu (2004) reported that the eating behaviours of the students who studied in health sciences were better than the others. Also, in the study conducted by Ermiş et al (2015) with the participation of 1105 students, it has been found that the students who were studying in the health sciences were more conscious of the health and nutrition related behaviours than the students who were studying in other departments. It can be thought, the fact that the students who studied in the health sciences have better eating behaviours than the other departments can be considered as a result of these students are having more opportunities to get healthy nutrition educations during their university life.…”
Section: Discussionmentioning
confidence: 99%
“…Veri toplama araçlarından ilki olan "Öğrenci tanıtım formu", öğrencilerin sosyo-demografik özellikleri ve beslenme alışkanlıklarına ilişkin verileri belirlemek için araştırma tarafından literatür taranarak hazırlanmıştır. [1][2][3]7,[13][14][15]18 Bu formda öğrencilerin; yaş, cinsiyet, bölüm, sınıf, kiminle yaşadığı, boy (cm), vücut ağırlığı (kg), beden kitle indeksi (BKİ), akademik başarı notu, ana öğünleri tüketimleri, yemek yeme hızı, gece yeme alışkanlığı, atıştırma şeklinde yeme durumu, fast-food yeme sıklığı, sağlıklı beslendiğini düşünme durumu, günlük televizyon izleme süresi gibi özelliklerini kapsayan sorular bulunmaktadır. Öğrencilerin beslenme alışkanlıklarını belirlemek amacıyla kullanılan BAİ'de Demirezen ve Coşansu tarafından geliştirilmiştir, beşli likert tipindedir ve altı maddeden oluşmaktadır.…”
Section: Araştirmanin öRneklem Ve Katilimcilarin öZelli̇kleri̇unclassified
“…gerekli besin maddelerinin uygun zaman aralıklarında yeterli düzeyde tüketilmesi sağlıklı beslenmenin en temel amaçlarındandır. [3][4][5] Bu nedenle, bireylerin sağlıklı beslenme alışkanlığı kazanması ve bu alışkanlığı yaşam boyu devam ettirebilmesi esastır.…”
unclassified